Atitudes de adolescentes em relação à velhice - Parnow, Beatriz Silvana (2024)
The significant growth of the elderly population fosters greater intergenerational coexistence, which can also be influenced by attitudes towards old age. Attitudes envolve what people think, feel, and how they would like to behave towards na atitudinal object. Understanding people’s attitudes cana id in comprehendind behaviors, as the componentes of atitude (information, affection, and action) tend to be congruente, promoting certain regularity in relation to the environment. In this contexto, it becomes essential to identify attitudes towards old age, as such understanding can contribute to the development of actions aimed at deconstructing stereotypes and prejudices directed at this age group. This was a quantitative, cross-sectional, and descriptive study, which aimed to investigate the attitudes of adolescents towards old age, identifying the frequency of positive and negative attitudes and the association between such attitudes with gender, age, and cohabitation with elderly people, involving 177 adolescents aged between 12 and 18 years. For data collection a questionnaire was applied covering socio-demographic aspects and the Attitude Towards Old Age Assessment Scale (Neri Scale). Data was analyzed descriptively and presented in mean, standart deviation, and absolute and relative frequencies. To verify the normality of the quantitative variables, the Kolmogorov-Smirnov test was used. For comparing the variables of gender and cohabitation whith elderly people with the total scores and domains of the Neri Scale, the independente t-test (total score) and the Mann-Whitney U test (domains) were used. The Sperman correlation coeficiente was used to verify the correlation between the participant’s age and the total and domain score of the Neri Scale. The classification regarding the strength of the correlation followed Cohen’s criteria (1988): r˂0.29 as a small correlation; 0.30≤r≤0.49 as a moderate correletion; and r˃0.50 as a strong correlation. In all tests, p˂0.05 was adopted. All statistical analyses were performed in the SPSS program (Statistical Package for the Social Science) version 22.0. The majority of the adolescents were female (53.1%), aged between twelve and fourteen years (80.2%), and did not reside with an elderly person (71.8%). The attitudes towards old age showed a generally positive trend, with associations identified with gender, where male adolescents presented more positive attitudes in the total scale assessment (p=0.042*) and in the agency (p=0.033*) and persona (p=0.008*) domains; and in cohabitation with elderly individuals, which showed more positive attitudes in those living with the elderly, in the social relationship domain (p=0.017*). No significant correlations with the adolescents' age were found. The results highlighted that adolescents' attitudes, although showing a generally positive trend, were diverse, suggesting old age as a life phase permeated by both positive and negative aspects. Further studies are suggested to identify factors impacting attitudes towards old age.